A structural model of information privacy concerns toward hospital websites. Issue 3 (6th July 2015) - Kuo, Kuang-Ming; Talley, Paul C.; Ma, Chen-Chung
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to propose and empirically test a theoretical model that considers the predictors of an individual's perceptions of information privacy, and also how it relates to his/her behavioral intention toward approaching hospital web sites. Design/methodology/approach – This paper collects data using survey methodology. A total of 331 usable participants are gathered and analyzed via structural equation modeling. Findings – Significant predictors of information privacy concerns include a stated online privacy policy and a hospital's reputation. Further, online privacy policy predicts a hospital's reputation. Finally, hospital reputation and information privacy concerns significantly predict an individual's behavioral intention toward approaching hospital web sites. Research limitations/implications – The study confirmed that an online privacy policy and reputation can effectively alleviate specific information privacy concerns; therefore, this may indicate that these two factors should be considered whenever investigating individuals' information privacy concerns. Practical implications – To acquire a good reputation and to diminish individuals' information privacy concerns toward hospital web sites, hospitals should pay attention to the posting of an online privacy policy and communicating such policies to given individuals. Originality/value – This paper fulfils the gap of exploring the relationship among online privacy policy, organization reputation, and information privacy concerns. Further, the hypothesized model and its findings could also provide useful information for managers who are intent on boosting hospital web site usage frequency patterns.